Is Prostitution a Profession? Should it be Legalized and Treated as Such? Group Debate Presentations - Blakely, Kristen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
You do not have to agree with the side of the debate that you present. You may choose to present the side with which you disagree. It is quite possible that you may be undecided on the issue. In any case, these debates are meant to be friendly and are designed for us as a class to explore a contemporary gendered debate and look at the different issues and arguments. Presenters are merely acting as facilitators in this process.